Near‐Infrared Lasing in Four‐Zigzag Edged Nanographenes by 1D versus 2D Electronic π‐Conjugation. (16th July 2021) - Muñoz‐Mármol, Rafael; Gordillo, Fernando; Bonal, Víctor; Villalvilla, José M.; Boj, Pedro G.; Quintana, José A.; Ross, Aaron M.; Paternò, Giuseppe M.; Scotognella, Francesco; Lanzani, Guglielmo; Derradji, Amel; Sancho‐García, Juan C.; et al.
Abstract: The search of compounds emitting in the near‐infrared (NIR) has been accelerated owing to their use in biomedical and telecommunications applications. In this regard, nanographenes (NGs) are attractive materials adequate for integration with other technologies, which have recently demonstrated amplified spontaneous emission (ASE) and lasing across the visible spectrum. Here, the optical and ASE properties of four‐zigzag edged NGs of the [ m, n ] peri ‐acenoacene family are reported, whose size is increased through conjugation extension by varying n (from 3 to 5) while keeping m = 2. Results show that such 1D conjugation extension method is more efficient in terms of shifting the photoluminescence (PL) to the infrared (PL at 710 nm in the larger compound, PP‐Ar) than through 2D conjugation extension as in previously reported NGs (PL at 676 nm with the largest compound FZ3, with n = 3 and m = 4). Additionally, PP‐Ar shows dual‐ASE (at 726 and 787 nm), whose origin is elucidated through Raman and transient absorption spectroscopies. These compounds' potential for red and NIR lasing is demonstrated through the fabrication of distributed feedback lasers with top‐layer resonators. This study paves the way towards the development of stable low‐cost all‐plastic NIR lasers. Abstract : Extending the conjugation of four‐zigzag edged nanographenes (NGs) in 1D is shown to be a very successful method (significantly better than in 2D) to shift their photoluminescence and laser emissions towards the infrared. The convenience of these NGs for near‐infrared lasing is demonstrated with the manufacture of very stable distributed feedback devices emitting between 730 and 795 nm.